The Immunoregulatory Role of Myeloid-Derived Suppressor Cells in the Pathogenesis of Rheumatoid Arthritis - Yan, Lan; Liang, Mingge; Yang, Tong; Ji, Jinyu; Jose Kumar Sreena, Goutham Sanker; Hou, Xiaoqiang; Cao, Meiqun; Feng, Zhitao (Frontiers in Immunology, 2020)
Myeloid-derived suppressor cells (MDSCs) are a group of cells, which regulate the immune response and exert immunosuppressive functions on various immune cells. Current studies have found that MDSCs have both anti-inflammatory and pro-inflammatory effects in rheumatoid arthritis (RA) and its animal models. MDSCs inhibit CD4+ T cells, which secrete pro-inflammatory factors such as IFN-γ, IL-2, IL-6, IL-17, and TNF-α by the inhibition of iNOS, ROS, and IFN-γ, and promote the production of anti-inflammatory factor IL-10. MDSCs can suppress dendritic cells by reducing MHC-II and CD86 expression; MDSCs can expand Treg cells in vitro under the action of IL-10; MDSCs can inhibit B cells through NO, PGE2; MDSCs can promote the response of Th17 cells by secreting IL-1β. As one of the precursor cells of osteoclasts, MDSCs can differentiate into osteoclasts by activating the NF- κB pathway in IL-1α. Therefore, our study reviews the research progress of MDSCs in RA, aiming to provide ideas for revealing the important role of MDSCs in RA.